Opportunities and barriers to the development of Poland in the field of renewable energy sources as compared to the European Union - Muszyński, Robert; Kocur-Bera, Katarzyna (International Conference “Environmental Engineering”, 2020)
Today, almost all of civilisation is based on energy. To a large extent, energy is being continuously acquired from non-renewable raw materials deposited in the Earth’s crust. Renewable sources provide alternative, infinite energy resources, particularly solar radiation, wind power and water movement. The Paris Agreement envisages the complete abandonment of fossil fuels by the year 2050 for all EU Member States. From a technical point of view, a complete transition to renewable energy sources (RES) is very difficult to achieve. In the case of Poland, the way to 100% RES is longer and more complex than in most EU countries. The main purpose of the conducted analysis was to thoroughly assess the possibilities for obtaining energy from inexhaustible sources as well as the benefits of various procedures in order to develop an optimal set of solutions. The aim of the presented study is to indicate the possibilities for the development of construction investments in the field of renewable energy sources that have an inseparable impact on spatial management. To achieve this aim, the method of research of the available literature and legislation was applied.
Keywords: renewable sources; natural energy; climate change; land management